Analysis of strain bursts during nanoindentation creep of high‐density polyethylene. Issue 11 (22nd July 2015) - Zare Ghomsheh, Mohammad; Spieckermann, Florian; Polt, Gerald; Wilhelm, Harald; Zehetbauer, Michael
<x xml:space="preserve">Abstract</x> Systematic studies were conducted of discrete deformation processes occurring during nanoindentation creep of polyethylene with respect to load and loading rate, indicating dislocation‐mediated plasticity.<boxed-text content-type="graphic" id="pi4967-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>